Composition of public investment and fiscal federalism: panel data evidence from Europe - Andreas Kappeler; Timo Välilä (European Investment Bank (EIB), 2007)
We present some stylised facts about the composition of public investment in Europe and analyse its determinants, with a special focus on the role of fiscal decentralisation. The empirical analysis is conducted both for levels of different types of public investment and for their shares in total public investment. The results suggest that fiscal decentralisation boosts economically productive public investment, notably infrastructure, and curbs the relative share of economically less productive public investment, such as recreational facilities. While not readily reconcilable with the traditional theory of fiscal federalism, especially as regards the provision of local public goods, these findings can be interpreted in terms of the literature on fiscal competition, with not only tax rates but also the quality of public expenditure weighing in firms' location decisions.
Keywords: H54; H77; H72; C23; C24; 330